Charge‐Transfer Cocrystal via a Persistent Radical Cation Acceptor for Efficient Solar‐Thermal Conversion. (23rd March 2022) - Xu, Jieqiong; Chen, Qian; Li, Shengkai; Shen, Jiachao; Keoingthong, Phouphien; Zhang, Liang; Yin, Zhiwei; Cai, Xinqi; Chen, Zhuo; Tan, Weihong
Abstract: Designing organic charge‐transfer (CT) cocrystals for efficient solar‐thermal conversion is a long‐sought goal but remains challenging. Here we construct a unique CT cocrystal by using a persistent 2, 2′‐azino‐bis(3‐ethylbenzothiazoline‐6‐sulfonic acid) radical cation (ABTS +. ) as the electron acceptor. The strong persistency and electron affinity of ABTS +. endow a high degree of electron delocalization between ABTS +. and the 3, 3′, 5, 5′‐tetramethylbenzidine donor. Together with the intrinsic long‐wavelength absorption of ABTS +., the synthesized cocrystal can effectively capture the full solar spectrum and show distinguished photothermal efficiency. Such a cocrystal is further used for solar‐driven interfacial evaporation, and a high evaporation rate of 1.407 kg m −2 h −1 and a remarkable solar‐to‐vapor efficiency of 97.0 % have been achieved upon 1 sun irradiation. This work indicates the enormous prospects for charge transfer‐based functional materials through rational radical cation engineering. Abstract : A unique charge‐transfer cocrystal is constructed via a persistent 2, 2′‐azino‐bis(3‐ethylbenzothiazoline‐6‐sulfonic acid) radical cation (ABTS +. ) electron acceptor. The strong electron affinity and long‐wavelength absorption of ABTS +. enable the resultant cocrystal with a full solar spectrum absorption, which yields an evaporation rate of 1.407 kg m −2 h −1 and a solar‐to‐vapor efficiency of 97.0 % in solar‐driven interfacial evaporation.